SOME 3D METAL COMPLEXES WITH 2,6-PYRIDINEDICARBOXYLIC ACID: SYNTHESIS AND APPLICATIONS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article discusses the synthesis of coordination compounds of selected 3d-series metals (Fe(III), Co(II), Ni(II), Cu(II), Zn(II)) with 2,6-pyridinedicarboxylic acid (dipicolinic acid, H₂pydc), as well as their structural features and application prospects. 2,6-Pyridinedicarboxylic acid is a tridentate (N,O,O) ligand containing one nitrogen donor and two carboxylate groups, which enables the formation of stable chelate complexes.